POTRET REFORMASI HUKUM DI INDONESIA PASCA REFORMASI TAHUN 1998 - Umbu Lily Pekuwaly (Masalah-Masalah Hukum, 2012)
Reformation of law past total reformation in may 1998 not yet progress reach that significant. Reformation of law as mainly agenda prominent limited at substancial of law with for times amandemen constitution 1945 and than establishment the institution of law enforcer for to support law enforcement like Yudicial commission and Court of Constitution. However, law enforcement that just and without discrimination as reformation ideally in law aspect untill now not perfect. Law enforcement tend discriminative beside that in law enforcement practice still has happened judicature mafiaKeywords : Reformation of law, law enforcement and Justice